Mobile Phones and Crime: the Protective Effect of Mobile Network Infrastructures - Felka, Patrick (Journal of quantitative criminology, 2020)
In this study, we investigate the relationship between mobile networks and crime by exploiting the temporal and spatial properties of crime and the exogenous occurrence of mobile network outages (MNOs) in San Francisco, (CA) from 5th March 2017 to the 24th March 2018.